Comparative study of diclofenac suppository with tramadol suppository in addition to acetaminophen for post caesarian analgesia - Hooda, Reetu; Pathak, Prachi; Chavhan, Rahul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Pain after emergency and elective caesarean section may adversely affect patient’s recovery and breastfeeding initiation. The aim of present study was to compare the analgesic efficacy of diclofenac suppository-intravenous acetaminophen (APAP) combination, tramadol suppository-intravenous APAP combination and intravenous APAP alone for postoperative pain relief after caesarean section. Methods: We designed a randomized double-blind control study. Three hundred parturient scheduled for caesarean section were randomized to receive diclofenac rectal suppository (100 mg), tramadol rectal suppository (100 mg) or glycerin rectal suppository in Group A, B and C respectively (100 parturient in each group). All the women routinely received 1000 mg acetaminophen intravenously. Assessment of pain was done using a visual analogue scale (VAS) at 0, 1, 6, 12, 18 and 24 hours. injection Pentazocine 0.3 mg/kg IV was given as rescue analgesia when VAS score > 30. Results: The mean VAS score was significantly higher in Group C as compared to Group A and Group B (p value < 0.001). This suggests better efficacy of multimodal treatment as compared to monotherapy. Group A as compared to Group B showed better efficacy in term of VAS score at 12 and 18 hours (p = 0.05, p = 0.02 respectively). Conclusions: We found that when controlling for socio-demographic characteristics, combination of either diclofenac or tramadol suppository with acetaminophen has significantly better results when compared with monotherapy of acetaminophen alone in post-operative analgesia after caesarean section. However, the combination of diclofenac suppository has proved to be superior in comparison to tramadol suppository.